Fluctuations and individual differences in empathy interact with stress to predict mental health, parenting, and relationship outcomes - Shalev, Ido; Eran, Alal; Uzefovsky, Florina (Frontiers in Psychology, 2023)
Introduction: Empathy is a complex, multifaceted ability allowing for the most basic forms of social communication and plays a prominent role in multiple aspects of everyday lives. In this intensive longitudinal study, we assessed how empathy interacts with stress to predict central domains of psychosocial functioning: mental health, romantic relationships, and parenting. Methods: Fluctuations and individual differences in empathy were assessed across eight time points, where participants from the general population (N = 566) self-reported their empathy, stress, depressive symptoms, romantic satisfaction, and parental functioning. Results: Both trait and state aspects of empathy were associated with all psychosocial outcomes, with state empathy showing a stronger effect. Additionally, empathy components interacted with stress - emotional empathy better-predicted outcomes under high stress, while cognitive empathy under low stress. Discussion: Our findings advance the theoretical understanding of empathy, emphasizing the effects of state-dependent empathy fluctuations on our everyday mental and social lives.